(untitled) (World Bulletin of Management and Law, 2022)
The process of delivering the service to the largest number of targeted and non-targeted people needs several means and the latest model, so the communication campaign goes through several stages starting from identifying the targeted people to evaluating the results, where the current system has become after the progress and development brought about by the technological revolution and the speed of achievement In many businesses, which requires heading towards searching for an alternative as a faster way to market the products of the economic unit, and this requires the unit to master the concepts and tools of in-depth communication to reach its goal, and the research reached a number of conclusions, the most important of which is that communication is a broad and comprehensive concept related With the parties in contact, but one of the most important recommendations recommended by the research is to reach the target consumer, the unit must work the communication mix, which is the effective element to influence consumer behavior